1995
DOI: 10.1103/physrevb.52.8121
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of carbon, silicon, and hydrogen complexes in AlAs, GaAs, andAlxGa1

Abstract: The results of a comprehensive Green's-function calculation are reported for the structure and dynamics of the amphoteric behavior of silicon [Sio,~«~, Si~, ], and the acceptor nature of beryllium and carbon IBeo,~A&~, CA, I impurities in GaAs, A1As, and AI"Ga& "As. Impurity vibrational modes are studied for (i) the nearest-neighbor CA, -A1G, pairs (C2"symmetry) in Al Ga& As (for x &0.04), (ii) the secondnearest-neighbor [e.g., C",-A1(Ga)-C«, Si",-As-Be~~] pairs (C~" /C, symmetry) in A1As (GaAs), and (iii) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The results of the MREI calculation are presented in Table 1 and are in agreement with existing infrared reflectivity data [10,11] and Raman scattering results [3,4,12,13]. According to the MREI model, a ternary alloy A and n h = 2 10 17 cm -3 .…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The results of the MREI calculation are presented in Table 1 and are in agreement with existing infrared reflectivity data [10,11] and Raman scattering results [3,4,12,13]. According to the MREI model, a ternary alloy A and n h = 2 10 17 cm -3 .…”
Section: Resultssupporting
confidence: 70%
“…6, which are calculated based on a microscopic second-neighbor rigid ion model (RIM) [13]. The separation between the optical and acoustic regions increases across CdTe and MnTe.…”
Section: Resultsmentioning
confidence: 99%
“…However, the doping center is still not clearly identified [8]. In spite of excellent thermal stability for many implanted acceptors into GaN 19], numerous attempts to use such dopants as Be, Si and Cd were largely unsuccessful [3,7,10], though Be has been a commonly used p-type dopant in MBE growth of GaAs based materials [11,12]. At the same time, Zn-doped InGaN/AIGaN double-heterostructures [13,14] revealed superbright blue and green emissions and showed that successful p-type Mg doping is not the only one possible.…”
Section: Introductionmentioning
confidence: 99%